The relationship between communication, customer knowledge and customer loyalty in Saudi Arabia insurance industry companies - Alawni, Mohammed Saad; Yusoff, Rushami Zien; Al-Swidi, Abdullah Kaid; Al-Matari, Ebrahim Mohammed (Emerald Group Publishing Limited, 2015)
The main target of this article is to examine the relationship between communications, customer knowledge and customer loyalty in insurance companies in Saudi Arabia.This study adopted Partial Least Squares Structural Equation Modeling (PLSSEM) to test the association between communication, customer knowledge and customer loyalty.The sample comprised of 399 from insurance companies in Saudi Arabia and data was obtained from questionnaires distributed to the sample. Moreover, the questionnaire was adopted from many authors as explained in methodology section.This article found a positive and significant relationship between communication and customer loyalty.In the same path, this study found that customer knowledge has a positive and significant effect on customer loyalty.Moreover, this study has significant contributions in the theoretical, practical and policy market that may be integrated together in order to improve customer loyalty. Finally, the limitation and future recommendations were provided at the end of this study.